Recurrent Rhinovirus Detections in Children Following a Rhinovirus-Induced Wheezing Exacerbation: A Retrospective Study - Hürdum Sofie Halmø; Zhang, Guicheng; Khoo, Siew-Kim; Bizzintino, Joelene; Franks, Kimberley Marie; Lindsay, Katie; Keil, Anthony David; Cox, Desmond William; Goldblatt, Jack; Bochkov, Yury Alexandrovich; Gern, James; Ulrik, Charlotte Suppli; et al. (International Journal of Pediatrics and Child Health, 2015)
Introduction: It is unclear if children with a rhinovirus (RV)-induced wheezing exacerbation are more susceptible to viruses longitudinally, and whether a parental history of asthma and/or allergy impacts their susceptibility. The objective of this study was to determine if RV, RV-A and RV-C related wheezing exacerbations in children were associated with prior or subsequent viral detections and investigate the role of parental history of asthma and allergy. Materials and methods: Children presenting to hospital with acute wheeze were prospectively recruited and tested for respiratory viruses. Data on viruses detected in other respiratory samples (May 1997 to December 2012) were collected from hospital microbiology records and additional RV testing was performed on stored hospital respiratory samples (September 2009 to December 2012). A positive parental history was defined as either parent with self-reported asthma and/or allergy. Results: At recruitment, RV was detected in 69.2% of samples from children with an acute wheezing episode (n=373, 0–16 years of age), with RV-C the most common virus (65.5%). Children with a history of parental asthma and/or allergy and RV at recruitment had a 14-fold increased incidence rate ratio (IRR) of subsequent RV detection (IRR 14.0, 95% CI 1.9–104.1; p=0.01) compared with children without RV at recruitment. Children without this parental history had a reduced incident rate ratio for samples assessed during this time (IRR 0.5, 95% CI 0.3–0.9; p=0.03). Conclusion: Children with a parental history of asthma and/or allergy may become more susceptible to recurrent symptomatic RV infections.